2016
DOI: 10.1039/c6fo01165a
|View full text |Cite
|
Sign up to set email alerts
|

The prothrombotic state associated with obesity-induced hypertension is reduced by cocoa and its main flavanols

Abstract: Our results showed that cocoa and its main flavanols may improve endothelial dysfunction and exert their antihypertensive effects by decreasing the prothrombotic state in rats fed a hypercaloric diet. Moreover, improvement of obesity-related metabolic disorders may also contribute to their BP-lowering effect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 76 publications
0
9
0
Order By: Relevance
“…In a trial conducted in rats, small doses of cocoa extract supplements were enough to counteract obesity and type 2 diabetes, providing new ideas about the possible application of cocoa supplements in the management of metabolic syndrome (19) . Likewise, another laboratory trial concluded that cocoa and its flavonoids could improve endothelial dysfunction and contribute with their reducing effect on arterial pressure (20) . Although polyphenols and their impact on obesity are still poorly known, some studies have suggested that they can have a positive effect on glucose regulation, adipogenesis, lipolysis, lipid metabolism and appetite control (21)(22)(23)(24) .…”
Section: Discussionmentioning
confidence: 99%
“…In a trial conducted in rats, small doses of cocoa extract supplements were enough to counteract obesity and type 2 diabetes, providing new ideas about the possible application of cocoa supplements in the management of metabolic syndrome (19) . Likewise, another laboratory trial concluded that cocoa and its flavonoids could improve endothelial dysfunction and contribute with their reducing effect on arterial pressure (20) . Although polyphenols and their impact on obesity are still poorly known, some studies have suggested that they can have a positive effect on glucose regulation, adipogenesis, lipolysis, lipid metabolism and appetite control (21)(22)(23)(24) .…”
Section: Discussionmentioning
confidence: 99%
“…Feed consumption was monitored daily, and body weight was measured weekly throughout the experiment. After the experimental period (week 8), rats were anesthetized with pentobarbital sodium (32 mg/kg intraperitoneally) after 12 h fasting [ 18 , 26 , 27 , 28 ]. The use of male Wistar rats was approved by the Ethics and Research Committee of the National School of Biological Sciences of National Polytechnic Institute from Mexico.…”
Section: Methodsmentioning
confidence: 99%
“…In line with this, the exposure of human endothelial cells to epicatechin inhibited endothelial NADPH oxidase, reduced superoxide and peroxynitrite levels, and consequently induced an increase in NO and cyclic guanosine monophosphate cellular levels ( 94 ). Furthermore, cocoa powder and epicatechin demonstrated to significantly decrease aortic oxidative stress and circulating markers related to impaired coagulation (von Willebrand factor, factor VIII, and fibrinogen) and inflammation (tissue necrosis factor-α, interleukin-6, interleukin-10, and C-reactive protein) ( 95 ). In vitro experiments show that CFs inhibit pro-inflammatory cytokines such as interleukin-2, interleukin-1β, and tissue necrosis factor-α, and positively modulate the expression of anti-inflammatory cytokines, such as interleukin-4 and transforming growth factor-β ( 92 , 96 98 ).…”
Section: Putative Mechanismsmentioning
confidence: 99%